153k views
0 votes
The expression 4x^2-px-7 leaves a remainder of -2 when divided by (x-3) find the value of p

User Motumbo
by
5.0k points

1 Answer

6 votes

The expression 4x^2-px-7 leaves a remainder of -2 when divided by (x-3). Then the value of p is 10.33

Solution:

Given the expression is
4x^2 - px - 7 leaves a remainder of -2 when divided by (x-3)

To find: value of p

x - 3 = 0

x = 3

Let
g(x) = 4x^2 - px - 7

Hence we can say,

g(3) = -2

Substitute x = 3 in g(x) we get,


g(3) = 4(3)^2 - p(3) - 7\\\\-2 = 4(3)^2 - p(3) - 7

On solving we get,

-2 = 4(9) - 3p - 7

-2 = 36 - 3p - 7

3p = 36 - 7 + 2

3p = 31


p = (31)/(3) = 10.33

Thus the value of p is 10.33

User Katu
by
5.1k points